Melioidosis – A Rare Cause of Neck Abscess in Immunocompromised - Nayana V G; saimanohar s; Dr.Nandini Raveendra; Sheetal Rai; Preethishree P (Bengal Journal of Otolaryngology and Head Neck Surgery, 2021)
Introduction